The SARS-CoV-2 Pandemic Impacts the Management of Swiss Pediatric Intensive Care Units - Soomann, Maarja; Wendel-Garcia, Pedro D.; Kaufmann, Mark; Grazioli, Serge; Perez, Marie-Helene; Hilty, Matthias P.; André, Maya C.; Brotschi, Barbara (Frontiers in Pediatrics, 2022)
The impact of the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) pandemic on pediatric intensive care units (PICUs) is difficult to quantify. We conducted an observational study in all eight Swiss PICUs between 02/24/2020 and 06/15/2020 to characterize the logistical and medical aspects of the pandemic and their impact on the management of the Swiss PICUs. The nine patients admitted to Swiss PICUs during the study period suffering from pediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 (PIMS-TS) and constituting 14% (9/63) of all SARS-CoV-2 positive hospitalized patients in Swiss children's hospitals caused a higher workload [total Nine Equivalents of nursing Manpower use Score (NEMS) points, p = 0.0008] and were classified to higher workload categories (p < 0.0001) than regular PICU patients (n = 4,881) admitted in 2019. The comparison of the characteristics of the eight Swiss PICUs shows that they were confronted by different organizational issues arising from temporary regulations put in place by the federal council. These general regulations had different consequences for the eight individual PICUs due to the differences between the PICUs. In addition, the temporal relationship of these different regulations influenced the available PICU resources, dependent on the characteristics of the individual PICUs. As pandemic continues, reflecting and learning from experience is essential to reduce workload, optimize bed occupancy and manage resources in each individual PICU. In a small country as Switzerland, with a relatively decentralized health care local differences between PICUs are considerable and should be taken into account when making policy decisions.